Are Different-Currency Assets Imperfect Substitutes? - Martin D. D. Evans; Richard K. Lyons (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper provides a new test for whether different-currency assets are imperfect substitutes. The test exploits that under floating rates, changing public currency demand has no direct effect on monetary fundamentals, current or future. Price effects from imperfect substitutability are clearly present: the immediate price impact of public trades is 0.44 percent per 1 billion dollar (of which, about 80 percent persists indefinitely). This estimate is applicable to intervention trades in the special case when they are indistinguishable from private trades (i.e., when interventions are sterilized, anonymous, and provide no monetary-policy signal).
Keywords: 330